Performance of multidetector computed tomography colonography compared with conventional colonoscopy. Issue 2 (1st August 2002) - Gluecker, Th; Dorta, G; Keller, W; Jornod, P; Meuli, R; Schnyder, P
Abstract : Background and aims: This was a prospective blinded study to compare computed tomography (CT) colonography, performed with multidetector arrays CT scan (MDCT), with conventional colonoscopy for the detection of colorectal neoplasia. Methods: Fifty patients were examined by MDCT after standard bowel preparation and rectal air insufflation in the supine and prone positions. Data sets were examined by one radiologist and one gastroenterologist blinded to the patient's history and colonoscopy results. Patients subsequently underwent colonoscopy on the same day, which served as the gold standard. Results: Nine of 11 lesions >10 mm (82%), 5/15 lesions of 6–9 mm (33%), and 1/42 polyps <5 mm (3%) were detected by MDCT colonography. One false positive result for a structure larger than 10 mm was described. Nineteen of 21 patients who had no lesions during conventional colonoscopy were considered free of lesions by MDCT colonography, yielding a per patient specificity of 90%. Conclusion: MDCT colonography provides good data quality and has good sensitivity and specificity for the detection of colonic lesions of 10 mm or more.